Gaya Kepemimpinan Kekeluargaan Dan Dinamika Multikultural Dalam Mendorong Inovasi Usaha Sablon Jopi Artscreen - Galuh Pravita Sari; Mutiara Aisyah Nur Rahmah; Jea Ananda Sari; Eza Paramitha; Muhammad Syaifur Rohman (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to examine the role of familial leadership and multicultural dynamics in fostering innovation at the Jopi Artscreen screen printing MSME. The research approach employed a descriptive qualitative method, gathering data through in-depth interviews with the owner and employees. The findings reveal that the owner implements a familial leadership style, evident in deliberation, casual conversations, and open dialogue in addressing issues. The multicultural dynamics emerging from the diversity of employees' regions of origin are handled via group activities and a humble leadership demeanor, fostering a cohesive work atmosphere. This inclusive organizational culture contributes to the rise of innovations, such as plans for creating a new brand that highlights social themes, skill enhancement, and the expansion of production equipment. Moreover, the familial culture aids in tackling internal obstacles, especially those concerning work motivation and production oversight. This study concludes that the blend of familial leadership and transparent management of cultural diversity proves effective in bolstering collaboration, intercultural communication, and establishing an environment favorable to innovation at the Jopi Artscreen MSME.